2013
DOI: 10.1097/01.mib.0000438356.84263.3b
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis and Gingivitis in Inflammatory Bowel Disease

Abstract: IBD, and especially perianal disease in CD, is associated with periodontitis. Optimal therapeutic strategies should probably focus on treating both local oral and systemic inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
120
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(132 citation statements)
references
References 26 publications
7
120
2
3
Order By: Relevance
“…Poor dental health can adversely affect a number of systemic conditions and diseases, such as cardiovascular diseases (4), diabetes (5), respiratory diseases (6), and inflammatory bowel diseases (7), and can even lead to preterm delivery (8,9) and systemic disease (10)(11)(12). However, the associations between periodontal disease and sperm abnormalities have not been adequately investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Poor dental health can adversely affect a number of systemic conditions and diseases, such as cardiovascular diseases (4), diabetes (5), respiratory diseases (6), and inflammatory bowel diseases (7), and can even lead to preterm delivery (8,9) and systemic disease (10)(11)(12). However, the associations between periodontal disease and sperm abnormalities have not been adequately investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Periodontitis is related to rheumatoid arthritis, and treatment for the former has an effect on both the latter and systemic inflammation (Payne et al, 2015). In addition, preeclampsia (Ha et al, 2014), other complications during pregnancy (Zi et al, 2015), and inflammatory bowel disease (Vavricka et al, 2013), amongst other conditions, have been shown to be associated with chronic periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…However, since then further prospective trials have identified that IBD patients have higher provenances of periodontal disease, deeper pocket depth and more clinical attachment loss. 55,56 Malnutrition Malnutrition is very prevalent within the IBD population. Literature has previously estimated this number to be almost one in four outpatients, and almost nine out of ten inpatients.…”
Section: Periodontal Diseasementioning
confidence: 99%